Research advances in treatment methods and drug development for rare diseases - Han, Qiaoqiao; Fu, Hengtao; Chu, Xiaoyue; Wen, Ruixin; Zhang, Miao; You, Tao; Fu, Peng; Qin, Jian; Cui, Tao (Frontiers in Pharmacology, 2022)
As the incidence of rare diseases increases each year, the total number of rare disease patients worldwide is nearly 400 million. Orphan medications are drugs used to treat rare diseases. Orphan drugs, however, are rare and patients often struggle to utilize them and expensive medications during treatment. Orphan drugs have been the focus of new drug research and development for both domestic and international pharmaceutical companies as a result of the substantial investment being made in the field of rare diseases. Clinical breakthroughs have been made in every field, from traditional antibodies and small molecule drugs to gene therapy, stem cell therapy and small nucleic acid drugs. We here review the therapeutic means of rare diseases and drug development of rare diseases to show the progress of treatment of rare diseases in order to provide a reference for clinical use and new drug development of rare diseases in China.